Wheat Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Olson, Brian L.S. (My University, 2011)
This publication provides estimated cost and returns for forward farm planning for wheat in north central Kansas.
MF2158_2011_12
Keywords: MF2158; Crops; Economics; MF